Univocity and Analogy: A Comparative Study of Gilbert Ryle and Martin Heidegger (Diametros, 2012)
The work of Gilbert Ryle maintains a notable proximity to the philosophical disposition assumed by the phenomenology of Martin Heidegger. This is due largely to their critiques of the Cartesian tradition of philosophical anthropology. By employing the metaphysical positions of univocity and analogy as a hermeneutical device, this study attempts to draw out the fundamental differences between the projects of Ryle and Heidegger. It is my contention that Ryle is not a phenomenologist precisely because he affirms the Scotist doctrine of the univocity of being. In contrast, Heidegger is a phenomenologist precisely because he disaffirms univocity in favor of a modified version of Thomistic analogy. By recalling this important debate in medieval metaphysics, it is possible to gain important resources for debate between the “analytic” and “continental” camps – at least insofar as those labels correspond to the figures of Ryle and Heidegger in a meaningful way.
Keywords: Gilbert Ryle; Heidegger; univocity; analogy